Developing a method for the assessment of axial load in arbitrary cross-sections of the column of pumping rods - Andrusyak, Andriy; Grydzhuk, Jaroslav; Dzhus, Andriy; Steliga, Ivan (Eastern-European Journal of Enterprise Technologies, 2017)
For accurate and objective evaluation of the stressed-strained state of a column of pumping rods (PR), it is necessary to have reliable information about axial loads that act in its cross-sections at different depth. That is why the purpose of present research is to develop a method for the evaluation of loading in the arbitrary cross-sections of a PR column taking into account actual operating conditions. In the paper we present constructed simulation models of PR columns, which consider their design features, paprameters of operating modes of rod borehole pumping plants (RBPP), the peculiarities of interaction between columns of pump-compressor pipes (PCP) and PR, the laws of change in efforts in the point of their hanging. Using a PR column as a mechanical communication channel between the wellhead and arbitrary cross-section, we established functions of change in the axial load along its length. This allows us to track the dynamics of its change and detect dangerous cross-sections in a PR column. Implementation of the models developed enables reproduction of the laws of change in the axial load during operation cycle for arbitrary cross-sections of PR column. Their existence is the basis for analysis of the stressed-strained state and for predicting the durability of elements in a PR column.